SOME ORGANIC CONSTITUENTS OF SCALES OF THE FISH CHANNA PUNCTATUS AT DIFFERENT STAGES OF GROWTH - Saraswat, R C (Indian Journal of Fisheries, 2011)
Changes with age in the aminoacid composition of arterial elastin have been studied by Lansing et al (1951) and the component amino acids of the protein of fish Labeo rohita at different stages of growth have been reported by Tiwari and Srivastava (1962). Ether extract (crude fat), nitrogen (crude protein) and aminoacid contents of the fins of the common cat fish Wallago attu have been quantitatively studied by Saraswat and Ram (1972) at different stages of growth.